ANALISIS YURIDIS PEMBUANGAN LIMBAH PABRIK GULA MADUKISMO DI LINGKUNGAN PADAT PENDUDUK - Iswara Prasetya Aji; Fatma Ulfatun Najicha (Indonesian State Law Review, 2021)
In carrying out environmental protection and management in the context of environmentally sustainable development, it is necessary to pay attention to the level of public awareness and global environmental developments, as well as international legal instruments related to the environment. People's awareness and life towards environmental protection and management has grown to the point where it is necessary to improve ways to achieve sustainable development goals from an environmental perspective. The regulations stipulated in Law no. 32 of 2009 concerning Environmental Protection and Management, especially in Chapter VII, states that hazardous and toxic materials and hazardous and toxic waste must be managed to minimize the waste treatment system, which poses a small risk to the environment, human survival and other organisms. By realizing this, hazardous and toxic materials and their waste need to be protected and managed properly.